The Elusive Quest for Inclusive Growth : Growth, Poverty, and Inequality in Asia - Balakrishnan, Ravi (IMF Working Papers; Working Paper ;, 2013)
This paper assesses how pro-poor and inclusive Asia's recent growth has been, and what factors have been driving these outcomes. It finds that while poverty has fallen across the region over the last two decades, inequality has increased, dampening the impact of growth on poverty reduction. As a result, relative to other emerging and developing regions and to Asia's own past, the recent period of growth has been both less inclusive and less pro-poor. Our analysis suggests a number of policies that could help redress these trends and broaden the benefits of growth in Asia. These include fiscal policies to increase spending on health, education, and social safetynets; labor market reforms to boost the labor share of total income; and reforms to make financial systems more inclusive.